2011
DOI: 10.1002/chp.20128
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Knowledge Brokering Within a Multidisciplinary Research Team

Abstract: Knowledge brokering (KB) may be one approach of helping researchers and decision makers effectively communicate their needs and abilities, and move toward increased use of evidence in health care. A multidisciplinary research team in Nova Scotia, Canada, has created a dedicated KB position with the goal of improving access to quality colorectal cancer care. The purpose of this paper is to provide an in-progress perspective on KB within this large research team. A KB position ("knowledge broker") was created to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
95
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(96 citation statements)
references
References 18 publications
0
95
0
1
Order By: Relevance
“…1,[3][4][5][6]10,[12][13][14][15][16]20,21,23,[28][29][30][31][32] Our review did not identify any other papers addressing knowledge broker experiences in rehabilitation. Although several studies 3,13,20,24 have suggested that knowledge brokers could help to close the knowledge-practice gap in health care, the effectiveness of such initiatives requires additional study. 13 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,[3][4][5][6]10,[12][13][14][15][16]20,21,23,[28][29][30][31][32] Our review did not identify any other papers addressing knowledge broker experiences in rehabilitation. Although several studies 3,13,20,24 have suggested that knowledge brokers could help to close the knowledge-practice gap in health care, the effectiveness of such initiatives requires additional study. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Although several studies 3,13,20,24 have suggested that knowledge brokers could help to close the knowledge-practice gap in health care, the effectiveness of such initiatives requires additional study. 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teams may struggle as they spend considerable time and effort trying to build a research program out of fundamental and largely incompatible assumptions and philosophies 99 . Moreover, working with non-academic stakeholders brings its own challenges, including navigating the professional differences (for example, language, culture) between academic and non-academic environments 100 , achieving an understanding of the limitations and realities of each other's work environments 101 , and perhaps at the extreme, risking substantial contributions or insights to the larger body of knowledge (scholarly activity) by focusing on solving very practical problems (engineering) 99 .…”
Section: Challenges Of Cross-disciplinary Collaborationmentioning
confidence: 99%